A trust-based conceptual framework on Open Government Data potential use - Zainal, Noor Zalina; Hussin, Husnayati; Mior Nazri, Mior Nasir (IEEE Explore, 2018)
Open Government Data (OGD) is a popular initiative by many governments around the world, as part of their Big Data implementation in the public sector. This paper attempts to propose a new model of measuring the level of use of open government data by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) and trust factors. The proposed model can operably extend the current UTAUT model in the context of OGD and suggest best guidelines for governments to implement OGD more extensively. This paper offers a valuable contribution by proposing a suitable model that measures technology usage in open data context from the perspective of the potential stakeholders.